Florida Solid and Hazardous Waste Regulation Handbook: Introduction - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
Current solid and hazardous waste law is a maze of statutes, regulations, and potential liabilities. This handbook is designed to act as your guide and as a first step in helping you recognize which agricultural and household activities may involve solid and hazardous wastes. It also provides an introduction to the agencies and statutes that govern solid and hazardous waste disposal. This is EDIS document FE441, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.